THE EFFECT OF WORK ENVIRONMENT, WORK MOTIVATION, AND WORK-LIFE BALANCE ON EMPLOYEE JOB SATISFACTION AT PT PG RAJAWALI II UNIT PG HGU JATITUJUH & SUBANG - Aan Anisah; Dharliana Hardjowikarto; Juwita (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the influence of the work environment, work motivation, and work–life balance on employee job satisfaction at PT PG Rajawali II Unit PG HGU Jatitujuh & Subang. The research employed a quantitative approach using a survey method. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results show that simultaneously the three independent variables significantly influence employee job satisfaction. Partially, work motivation and work–life balance have a positive and significant effect on job satisfaction, while the work environment does not have a significant effect. The coefficient of determination indicates that 43.7% of the variation in job satisfaction can be explained by the research model. These findings highlight the importance of managing employee motivation and maintaining a balance between work and personal life in order to improve job satisfaction.